The Prevalence of Iron Deficiency Anemia in Female Medical Students of Different Medical Colleges of Khyber Pakhtoonkhwa, Pakistan (Medical Forum Monthly, 2024)
Objective: Iron deficiency anemia (IDA) is very common in adolescent and adults, especially female. In medical students, it is caused by a number of causes, “including overwork, decrease appetite due to stress and unnecessary dieting”. Very little data is available at national level about these health conscious medical students. This “descriptive, cross sectional study, was conducted in public and private Medical colleges of KPK”. The main objective of the study was “to determine the Prevalence of IDA in female medical students of KPK”.Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the department of Pharmacology, Khyber Girls’ Medical College, Peshawar From December-2015 to May-2016.Materials and Methods 390-female medical students aged 19 to 24 years have participated in this study’. After formal consent and recording of their demographic information, “Hemoglobin (Hb) and Mean Corpuscular Volume (MCV) was done using digital Sysmex XT-4000i hematology analyzer”. Serum ferritin (S-Ferritin) was done using Architect I-2000 analyzer. The identity of all students was kept confidential. All students with, “Hb<12g/dl, MCV<76um3 and S-Ferritin <11ng/ml were labeled as having IDA and students having Hb>12g/dl, MCV>76um3 but S-Ferritin<11ng/ml were labeled as having Iron deficiency (ID), but not IDA”.Results: Complete data of all “390 students were available for further analysis”. The mean age of the students was 21±1 years. IDA was present in 6.66%(n=26/390) students, while ID was present in 41.54%(n=162/390) students. Normal iron status was found in 51.80%(n=202/390) students.Conclusion. It is concluded that “ID and IDA are very common in female medical students of KPK. All female medical students should be encouraged to take extra iron to replenish their iron store”.